CONSTRUCTION OF A PHYSICAL AND MATHEMATICAL MODEL OF THE GRAVITATIONAL FIELD - Kassenova Л.Ғ.; Yensebaeva Г.С.; Shuitenov Г.Ж. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The problem of gravitational field physics is to identify the relationship between the gravitational field and the expansion of the space-time continuum. Therefore, the creation of models, the study of which makes it possible to identify these relationships and express them in formulas, is relevant. In the modern theory of the gravitational field, small quantities appear, which are neglected in the derivation of formulas of practical application. This paper presents a model of the gravitational field that combines quantum properties with the expansion of the space-time continuum. Also, using a simplified model of the coordinate system, the gravitational field of a stationary centrally symmetric object is studied and the limiting distance of the test particle capture by the gravitational field is calculated. Calculations made without neglecting small quantities gave interesting results: the limiting radius of capture by the gravitational field of the test particle; the formula for the mass defect of the black hole Schwarzschild; relations expressing the dependence of the quantities of quantum physics on the Hubble constant.